Analisis Kualitatif Terhadap Kepuasan dan Loyalitas Pelanggan Kedai Kopi Gayo Menggunakan Metode Grounded Theory - Maya Seruni Putri; Jerry Heikal (SAFE-Network, 2023)
This study aims to identify the constructs of customer satisfaction and loyalty at Gayo coffee shops in Takengon, Central Aceh. Researchers use the Grounded Theory method, as a tool for qualitative analysis. Researchers conducted in-depth interviews with Gayo coffee shop customers, at six different coffee shops in Takengon, Central Aceh. The analysis performed included open-coding of the data to identify categories and themes; axial-coding to link categories and themes; and selective-coding to identify core themes. The findings show that service is the main factor that constructs customer satisfaction and social interaction is the main factor that constructs customer loyalty at Gayo coffee shops in Takengon, Central Aceh.